Analisis Kebijakan Publik dalam Meningkatkan Kesejahteraan melalui BLT, BLTS, dan Penyaluran Beras di Kelurahan Cipete - Neng Yuliani; Rasti Rahmadinah; Khikmawanto Khikmawanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study aims to analyze the implementation of public policies in improving community welfare through the Direct Cash Assistance (BLT) Program, the Subsidized Direct Cash Assistance (BLTS), and rice distribution managed by the State Logistics Agency (BULOG) in Cipete Village. The research method used is a descriptive qualitative approach. Data collection techniques were carried out through interviews with policy implementers and beneficiary communities, direct observation of the aid distribution process, and review of relevant official documents and data. The results show that the BLT and BLTS programs play a significant role in helping low-income communities meet their basic needs and increasing household purchasing power, especially during unstable economic conditions. Meanwhile, rice distribution by BULOG supports community food security by providing access to staple foods at prices lower than market rates. Despite the positive impacts, the implementation of these three programs still faces various obstacles, including inaccurate beneficiary targeting due to imprecise and rarely updated data, delays in the distribution process, lack of information transparency, and suboptimal inter-agency coordination. Based on these findings, improvements are required, such as developing an integrated and technology-based data system, increasing information disclosure to the public, strengthening monitoring and periodic evaluation systems, and enhancing cooperation among related institutions. Optimizing the implementation of these social assistance programs is expected to create sustainable, equitable, and targeted improvements in community welfare.